Brief daily episode of normoxia inhibits cardioprotection conferred by chronic continuous hypoxia. Role of oxidative stress and BKCa channels - Neckár, Jan; Borchert, Gudrun H; Hlousková, Patricie; Mícová, Petra; Nováková, Olga; Novák, Frantisek; Hroch, Milos; Papousek, Frantisek; Ost'ádal, Bohuslav; Kolár, Frantisek (Current pharmaceutical design, 2013)
The purpose of the present study was to assess the impact of brief daily reoxygenation during adaptation to chronic continuous hypoxia (CCH) on protective cardiac phenotype. Adult male Wistar rats were kept at CCH (10% oxygen) for 5, 15 or 30 days; a subgroup of animals was exposed to room air daily for a single 60-min period. While 5 days of CCH did not affect myocardial infarction induced by 20-min coronary artery occlusion and 3-h reperfusion, 15 days reduced infarct size from 62% of the area at risk in normoxic controls to 52%, and this protective effect was more pronounced after 30 days (41%). Susceptibility to ischemic ventricular arrhythmias exhibited reciprocal development. CCH increased myocardial abundance of mitochondrial superoxide dismutase (MnSOD) without affecting malondialdehyde concentration. Daily reoxygenation abolished both the infarct size-limiting effect of CCH and MnSOD upregulation, and increased malondialdehyde (by 53%). Ventricular cardiomyocytes isolated from CCH rats exhibited better survival and lower lactate dehydrogenase release caused by simulated ischemia/reperfusion than cells from normoxic and daily reoxygenated groups. The cytoprotective effects of CCH were attenuated by the large-conductance Ca2+-activated K+ (BKCa) channel blocker paxilline, while the opener NS1619 reduced cell injury in the normoxic group but not in the CCH group. Daily reoxygenation restored the NS1619- induced protection, whereas paxilline had no effect, resembling the pattern observed in the normoxic group. The results suggest that CCH is cardioprotective and brief daily reoxygenation blunts its salutary effects, possibly by a mechanism involving oxidative stress and attenuation of the activation of mitochondrial BKCa channels.
Keywords: Rats; hypoxie; superoxiddismutasa; Malondialdehyde; Hypoxia; malondialdehyd; Rats, Wistar; mužské pohlaví; Oxidative Stress; glykosylace; Large-Conductance Calcium-Activated Potassium Channel alpha Subunits; krysa rodu Rattus; Superoxide Dismutase; vápníkem aktivované draslíkové kanály s vysokou vodivostí - alfa-podjednotky; kyslík; Glycosylation; zvířata; kardiotonika; Potassium Channels; draslíkové kanály; Cardiotonic Agents; potkani Wistar; Oxygen; oxidační stres; Male; Animals